Characterization of Hearing in Children in a Population Base Study in the City of Itajaí / SC - Roggia, Simone Mariotto; Broca, Vanessa Schereider; Pagnossim, Débora Frizzo; Debiasi, Tháicy Figueiró; Balen, Sheila Andreoli; Gondim, Lys Maria (International Archives of Otorhinolaryngology, 2009)
Introduction: Hearing is the sensorial system that helps mankind in the acquisition and development of the oral language and enables their insertion into the socio-cultural environment. Objective: To characterize the hearing of children since birth until 14 years and 11 months of age, living in Itajaí. Method: Prospective study whose population was composed by inhabitants of the urban region of the city of Itajaí, SC. All individuals living in the sorted houses were included in the audiological evaluation, and the collective, commercial and non-inhabited dwellings were excluded. The children older than 4 years old were evaluated as for the acoustic meatus, audiological selection in the frequencies of 1000, 2000 and 4000 Hz, research of acoustic reflexes and tympanometry. In the children younger that 3 years and 11 months the behavioral and transient evoked otoacoustic emissions evaluations were carried out. Results: From the 119 children evaluated, the occurrence of some kind of auditory deficiency was of 16.84% in the children older than four years, in the analysis of the best ear. No case of incapacitating auditory deficiency was found. When we matched the behavioral evaluation results of children aged up to three years and 11 months with the results from the tympanometry of the research of ipsilateral acoustic reflexes and transient otoacoustic emissions, we confirmed the occurrence of 59.10% of audiological alterations, and from these there were alterations predominantly in the tympanometry and acoustic reflexes, which suggested conductive problems. Conclusion: This confirms the importance of acting for the promotion and prevention of conductive hearing losses, by attempting to provide the children with the development of language and learning fully and effectively.